HUBUNGAN MOTIVASI ORANG TUA DENGAN KEMAMPUAN MENGENAL HURUF PADA SISWA KELAS B DI TK. AZHARIAH DESA SURO KECAMATAN MUARA BELITI KABUPATEN MUSI RAWAS - Lia Mardiyanti (Conciencia, 2017)
Kindergarten is one of the early childhood education institutions found in the formal education pathway. In accordance with the objectives of TK according to the laws of the Republic of Indonesia No. 20 of 2003 concerning the First National Education system CHAPTER VI article 28 paragraph 3 reads: "Early childhood education in the formal education path is in the form of Kindergarten, Raudatul Athfal or other equivalent forms". Kindergarten Education is a form of Early Childhood Education on the Formal Education pathway that provides educational programs for children aged 4 to 6 years. This age of 4 to 6 is the most effective age for developing various potentials that children have. According to Muliawan Early childhood education is also called preschool education, playground, or kindergarten. Education in kindergarten is very important in the life of a child, because education is currently the basic capital for further development. For that kind of learning in kindergarten must be adjusted to the development of the child and provide a sense of security, comfort, fun and interest for the child and encourage courage. In the Republic of Indonesia Government Regulation No.19 of 2005 concerning Chapter education standards. IV Article 19 states that: the learning process in educational units is held interactive, fun, challenging, motivating, students to actively participate and provide sufficient space for initiatives, creativity and independence in accordance with the talents and physical and psychological development of students. Kindergarten education aims to help students develop a variety of potential both psychological and physical which includes moral and religious, social, emotional, independence, cognitive, language, physical / motoric and artistic values ​​to be ready to enter elementary school. The age of Kindergarten is a golden age, where children's physical, motoric, cognitive, language, social, emotional development develops very quickly. Learning activities in kindergarten are better known as play activities. The world of children is playing. Playing is the best way to develop the potential that exists in children. Playing is also one of the learning approaches in kindergarten. This is in accordance with the principle of learning Taman Kanakak, which is playing while studying, learning while playing.